2023
DOI: 10.3390/molecules28083571
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Rich Black Currant (Ribes nigrum) Ethanolic Gemmotherapy Extract Elicits Neuroprotective Effect by Preventing Microglial Body Swelling in Hippocampus and Reduces Serum TNF-α Level: Pilot Study

Abstract: Many plant-derived flavonoids are known for their anti-neuroinflammatory and anti-neurodegenerative effects. The fruits and leaves of the black currant (BC, Ribes nigrum) contain these phytochemicals with therapeutic benefits. The current study presents a report on a standardized BC gemmotherapy extract (BC-GTE) that is prepared from fresh buds. It provides details about the phytoconstituent profile specific to the extract as well as the associated antioxidant and anti-neuroinflammatory properties. The reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The last three compounds were classified as other phenolic compounds: p-coumaric acid glucose ester (4) and two compounds from the catechin group (1 and 5) (Table 2). Most of the identified compounds have previously been detected in blackcurrant leaf extracts [35][36][37][38]. In the phenolic compound profile obtained in the present work, 17 compounds were identical to those reported by D'Urso et al [36], who identified 31 phenolic compounds in 3 types of blackcurrant leaf extracts.…”
Section: Chromatographic Analysessupporting
confidence: 88%
“…The last three compounds were classified as other phenolic compounds: p-coumaric acid glucose ester (4) and two compounds from the catechin group (1 and 5) (Table 2). Most of the identified compounds have previously been detected in blackcurrant leaf extracts [35][36][37][38]. In the phenolic compound profile obtained in the present work, 17 compounds were identical to those reported by D'Urso et al [36], who identified 31 phenolic compounds in 3 types of blackcurrant leaf extracts.…”
Section: Chromatographic Analysessupporting
confidence: 88%
“…However, there is a paucity of data in the literature on the antimicrobial activity of plant parts, such as buds and young shoots, despite the fact that they contain many bioactive compounds and could have potent antimicrobial properties. In addition, recent studies have described the phytonutrient profile of some GTEs while also revealing their nutritional, antidiabetic and anti-inflammatory effects [40,48,51]. The phytonutrient composition of these GTEs also suggests that they may have antimicrobial properties, and this article presents relevant research data.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the antioxidant capacity of blackcurrant was found to vary depending on the season and cultivar [46]. In blackcurrant buds, the most common phenolic compounds are gallic acid, hydroxycinnamic acid derivatives, several flavonols (glycosidealcoolics of quercetin, myricetin, kaempferol and isorhamnetin) and dihydroquercetin derivatives [20,48]. According to another study, the most common flavonols in blackcurrant buds are rutin, isoquercetin and astragalin [46,65].…”
Section: The Blackcurrant Gte Is Less Effective As a Microbial Growth...mentioning
confidence: 97%
See 1 more Smart Citation
“…Several components found in R. nigrum leaves, such as quercetin and anthocyanins, have anti-in ammatory, antioxidant, antiviral, antimicrobial, antibiotic-modulatory and other effects [22]. Some authors mention the neuroprotective effect of R. nigrum extracts [59].…”
Section: Discussionmentioning
confidence: 99%